CUSTOMER SATISFACTION LEVEL BETWEEN SHOPPING AT ONLINE SHOP AND OFFLINE SHOP AT THE CAMPUS OF THE DARUSSALAM INSTITUTE OF ISLAM (IAID) CIAMIS - Tazkiyah Ainul Qolbi; Rini Febriani; Agus Muslim (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2020)
This research was conducted to determine consumer satisfaction in shopping at online shops and offline shops. This study uses a quantitative approach because the data obtained is realized in the form of numbers and analyzed based on statistics. The results showed a difference in shopping satisfaction between the online shop and the offline shop. It is evidenced by obtaining significant results so that it can be concluded that the null hypothesis is rejected and the working hypothesis is accepted. The average student who does not like to shop at online shops is because they are not satisfied when shopping at online shops and get products that do not match what is stated in the description of the goods in the selected online shop. Usually, this happens in individual online shops on social media (not on trusted sites) and product brands that are not yet well known. However, the study results found several respondents who had shopped at a credible online shop and felt satisfied because it was as expected. As for the offline shop, the average student feels more satisfied because consumers can see firsthand the quality of the product and try the product to be purchased.